POLA PERUBAHAN HARIAN SUHU AIR DAN KECEPATAN ARUS DI SEKITAR GUNUNG API BAWAH LAUT MAHENGETANG - Stivano Mamarama; Armstrong Sompotan; Farly Tumimomor (Jurnal FisTa : Fisika dan Terapannya, 2020)
Indonesia an archipelago with 70% of the territorial waters stretching from the western end of Sumatra Island to the east of the Papua region, with the characteristic of the vast ocean of underwater structures in the Indonesian archipelago is also important to be discussed deeper. For that the underwater volcano research is very rare. This undersea research has been implemented and is a collaborative research study with DRPM's beginner lecturer SCHEME research with the title of Master of Umbrella research "The analysis and modeling of Temporal changes and partial fraction of the sea water temperature at the Mahengetang underwater volcano". Involving 3 UNIMA students. The expedition was held from 20 to 22 March 2019. Where one of the objectives of this research is to obtain the data on water temperature fluctuations and the current speed of the underwater volcano Mahengetang has shown the pattern of water temperature and the current velocity of sea water from the upstream and downstream transect. From the results of analysis and modeling showed that the hydrodynamics factor and geothermal energy. The results of the hydrodynamics analysis indicate that the current velocity relies on tidal activity. The results of analysis and modeling show that water temperature varies horizontally and vertically. The velocity of currents and the masses of warm water are associated with the pattern of spatial distribution of coral reefs. The results of this PHISYCS analysis became a reference to the content of water chemicals, and biotic components such as coral reefs and various biota that live in it.